An Integrative Framework for Evaluating Financial Sustainability In Post-Merger Consolidation: A CRITIC-RAWEC Analysis of Public Sector Banks in India - Arup Mukherjee; Ratnesh Chaturvedi; Smita (Journal of Asia Entrepreneurship and Sustainability, 2026)
The vitality of banks in any economy cannot be overstated, serving as the backbone of financial stability, and fostering economic growth through efficient capital allocation. Public Sector Banks (PSBs) in India are entrusted with the responsibility of ensuring financial inclusion, supporting key sectors, and maintaining stability in the financial system. Understanding the financial sustainability of these banks is imperative, given their crucial role in facilitating economic progress. Evaluating their financial sustainability becomes paramount to ensure their ability to meet the demands of a dynamic economic landscape. This paper introduces the Criteria Importance Through Intercriteria Correlation (CRITIC) - Ranking Alternatives with Weights of Criterion (RAWEC) approach as a novel method for assessing the sustainability of PSBs, marking the first implementation of this Multi-Criteria Decision Making (MCDM) technique in the context of banking evaluations. CRITIC, enables a comprehensive review of criteria, while RAWEC, refines the evaluation process by ranking alternatives based on these criteria. Decision-makers in the banking sector can leverage the insights derived from the CRITIC-RAWEC approach to formulate effective strategies, enhance financial resilience, and bolster competitiveness. This research contributes to the evolving landscape of financial sustainability assessment methodologies, showcasing the pertinence and efficacy of the CRITIC-RAWEC approach in the critical evaluation of PSBs in India.